The epistemic violence of transitional justice: a view from Sri Lanka - Grewal, Kiran Kaur (International journal of transitional justice, 2023)
In this article I explore the failures of transitional justice in post-war Sri Lanka. For most commentators this is simply explained in terms of a lack of political will. However, I argue that beyond this transitional justice in Sri Lanka is a story of epistemic violence. This is a result of its over-reliance on abstract, universalist liberal democratic theory that fails to properly grasp the historical, cultural and socio-political specificity not just of the locations where transitional justice is proposed but of the conceptual foundation of transitional justice itself. As a result, transitional justice simultaneously discounts colonial legacies while reproducing colonial categories. In the case of Sri Lanka this has resulted in a failure to fully understand and address the root causes of conflict and an inability to see and draw upon resources for reconciliation, reparation and redress.